The Theme of the First Muslim Women in Chronographia of Theophanes the Confessor - Cecota, Błażej (Studia Ceranea, 2024)
This article concerns itself with a small fragment of Chronographia by Theophanes the Confessor. The fragment is devoted to the role of women in the rise and spread of Islam. Although generally considered to express anti-Islamic propaganda, upon closer examination, it is quite consistent with some Muslim traditions. The author interprets the fragment in a way that takes those traditions into account.